COVID-19 in Indonesia: Where Are We? - Iwan Ariawan; Hafizah Jusril (Acta Medica Indonesiana)
Since the 1st case officially confirmed on the last March 2020, Indonesia recorded more than 1000 new cases daily. The national trend shows no sign of decrease as 19 September 2020 the report sets a new mark of 4000 new cases in a day. The concept of controlling disease transmission relies on contacts suppression; and on the longer end, relies on vaccinations. As 27 September 2020, no vaccine is approved for use in the general population. Until then, countries should implement early, widespread, and strict disease mitigation strategies. While much remains to be learned on COVID-19, global evidence assert at least three strategies at the population level contributes to flatten the curve: mobility restriction, testing and isolation and rigorous contact-tracing.